Analisis Penggunaan Soal Hots pada Materi Fungsi Kuadrat terhadap Pencapaian Hasil Belajar Matematika Siswa - Parka, Amelia; Faizatussa’diah; Safa’at, Prima Ganda; Yuliabsyah, Siti Marwiyah; Firdaus, Talenta Zacki; Miharta, Yuan Pandu; Frischila, Yunike; Agustinsa, Ringki (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the impact of using HOTS-based questions on mathematics learning outcomes in the topic of quadratic functions at the high school level. Adopting a qualitative methodology with a descriptive pattern, data collection was conducted through three instruments: direct observation, interviews with respondents, and document analysis involving 10th-grade students of SMAN 6 Bengkulu City. The findings indicate that the implementation of HOTS-based questions significantly contributes to enhancing students' higher-order thinking skills, particularly in the aspects of C4 (analyzing), C5 (evaluating), and C6 (creating). However, post-test results reveal suboptimal achievements, with the majority of students still facing challenges in solving HOTS-based problems. Based on these results, it is recommended that educators continuously innovate teaching strategies and consistently incorporate HOTS-based questions to foster students' critical and innovative thinking skills.